Genetic Predictors of Long-term Response to Antitumor Necrosis Factor Agents in Pediatric Inflammatory Bowel Disease. Issue 4 (October 2020) - Salvador-Martín, Sara; Bossacoma, Ferrán; Pujol-Muncunill, Gemma; Navas-López, Víctor Manuel; Gallego-Fernández, Carmen; Viada, Javier; Muñoz-Codoceo, Rosana; Magallares, Lorena; Martínez-Ojinaga, Eva; Moreno-Álvarez, Ana; Solar-Boga, Alfonso; Segarra, Oscar; et al.
ABSTRACT: Objectives: Inflammatory bowel disease (IBD) is more complex in children and they will have to live with the disease for much longer. For this reason, it is necessary to optimize treatment. The polymorphisms associated with the response to anti-tumor necrosis factor (TNF) drugs in adults with IBD have not been analyzed in children. The aim of the study was to identify genetic variants associated with the long-term response to anti-TNF drugs in children with IBD. Methods: An observational, longitudinal, ambispective cohort's study was conducted. We recruited 209 anti-TNF-treated children diagnosed with IBD and genotyped 21 polymorphisms previously studied in adults with Crohn disease (CD) using real-time PCR. The association between single-nucleotide polymorphisms (SNPs) and time-to-failure was analyzed using the log-rank test. Results: After multivariate analysis, 3 SNPs in IL10, IL17A and IL6 were significantly associated with response to anti-TNF treatment among patients diagnosed with CD (rs1800872-HR, 4.749 (95% confidence interval [CI] 1.156–19.517), P value < 0.05; rs2275913-HR, 0.320 [95% CI 0.111–0.920], P value  < 0.05; and rs10499563-HR, 0.210 [95% CI 0.047–0.947], P value 0.05, respectively). None of these SNPs were associated with response to infliximab in adults diagnosed with CD. Among patients diagnosed with ulcerative colitis (UC), 1 SNP in LY96 was significantly associated with response to anti-TNF treatment (rs-11465996-HR, 10.220 [95% CI 1.849–56.504] P value < 0.05). Conclusions: Genotyping of these DNA variants before starting treatment may help to identify children who are long-term responders to anti-TNF drugs, and thus tailor treatment of pediatric IBD. Abstract : Supplemental Digital Content is available in the text